2006
DOI: 10.1177/107110070602701219
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fibular Torsional Deformities after Surgery for Ankle Fractures with a Novel CT Method

Abstract: Of the 61 ankle fractures with ruptures of the syndesmotic complex, 25% showed torsional side-to-side differences of more than 10 degrees on proximal and distal CT planes. This CT technique correlated with the AOFAS score and could help determine when early operative revision is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 31 publications
4
51
0
9
Order By: Relevance
“…In our study, the most common error was a posterior fibular malpositioning in the tibiofibular incisura (III). Our findings are in line with a previous study cautioning, that the syndesmotic screw may be a factor leading to syndesmotic malpositioning (Vasarhelyi et al 2006, Nimick et al 2013…”
Section: Recognition Of "Red Flags"supporting
confidence: 82%
See 2 more Smart Citations
“…In our study, the most common error was a posterior fibular malpositioning in the tibiofibular incisura (III). Our findings are in line with a previous study cautioning, that the syndesmotic screw may be a factor leading to syndesmotic malpositioning (Vasarhelyi et al 2006, Nimick et al 2013…”
Section: Recognition Of "Red Flags"supporting
confidence: 82%
“…However, recent studies with computed tomography (CT) have revealed, that the rate of syndesmotic malreduction is higher than previously thought , Vasarhelyi et al 2006, Mukhopadhyay et al 2011, Franke et al 2012, Davidovitch et al 2013. There is substantial anatomic variability in the tibiofibular incisure (Elgafy et al 2010, Mukhopadhyay et al 2011, Lepojärvi et al 2013, and the risk for syndesmotic malreduction is especially high in patients with flatter tibiofibular articulations (Elgafy et al 2010).…”
Section: Syndesmosismentioning
confidence: 90%
See 1 more Smart Citation
“…Fracture comminution, poor bone quality, and technical errors may predispose a patient to residual displacement following ankle fracture surgery , Lübbeke et al 2012. Recent studies with CT scan have revealed that proper reduction of a syndesmotic injury is especially demanding , Vasarhelyi et al 2006, Miller et al 2009, Mukhopadhyay et al 2011, Franke et al 2012, Sagi et al 2012, Davidovitch et al 2013. In a large population based study with 57,183 patients, the rate of revision ORIF following ankle fracture surgery was 0.8% within the first three postoperative months (Soohoo et al 2009).…”
Section: Postoperative Malreductionmentioning
confidence: 99%
“…Eine in Fehlstellung fixierte Fibula führt jedoch zu einer Inkongruenz im oberen Sprunggelenk mit erheblichen Auswirkungen auf die Gelenkfunktion und -belastung [19]. Verschiedene klinische Studien zeigten ein deutlich schlechteres Outcome bei Patienten mit Syndesmosenfehlreposition im Vergleich zu korrekt in die Tibiainzisur reponierten Fibulae [3,[17][18][19].…”
Section: Introductionunclassified